Предмет: Алгебра,
автор: Echelonovec
Помогитеее,умоляю!!!
Приложения:
![](https://files.topotvet.com/i/f76/f76eaf7c7a7b310a7dcf9032dada551e.jpg)
Ответы
Автор ответа:
0
чтобы найти функцию обратную данной достаточно у и х поменять местами.
![y=6-2x\x=6-2y\2y=6-x\y=frac{6-x}{2}\\y=x^3-1\x=y^3-1\y^3=x+1\y=sqrt[3]{x+1} y=6-2x\x=6-2y\2y=6-x\y=frac{6-x}{2}\\y=x^3-1\x=y^3-1\y^3=x+1\y=sqrt[3]{x+1}](https://tex.z-dn.net/?f=y%3D6-2x%5Cx%3D6-2y%5C2y%3D6-x%5Cy%3Dfrac%7B6-x%7D%7B2%7D%5C%5Cy%3Dx%5E3-1%5Cx%3Dy%5E3-1%5Cy%5E3%3Dx%2B1%5Cy%3Dsqrt%5B3%5D%7Bx%2B1%7D)
Автор ответа:
0
Спасибо большущее!))
Похожие вопросы
Предмет: Математика,
автор: Midnight006
Предмет: Алгебра,
автор: stepanovctepas
Предмет: Астрономия,
автор: ssooovvaa
Предмет: Математика,
автор: сучкоруб
Предмет: Физика,
автор: Yansik15